Розвиток інституту глави держави: досвід і сучасність України - Яковлєв, А. А. (Право, 2016)
У статті визначено основні етапи конституційного становлення та розвитку інституту глави держави у незалежній Україні, проаналізовано генезу функцій цього органу державної влади, а також охарактеризовано основні елементи конституційно-правового статусу глави держави. Автор досліджує роль глави держави в процесі триваючої нині конституційної модернізації. Дається комплексна характеристика конституційних перспектив зміни форми правління в Україні з урахуванням досвіду політичної реформи 2004 та 2014 рр., а також сучасного стану розвитку системи державної влади України. // The article defines the main stages of the Constitutional Formation and Development of the Institute of State of State in Independent Ukraine, analyzed the genesis of the functions of this state authority, as well as characterized by the main elements of the constitutional and legal status of the head of state. The author investigates the role of the head of state in the process of continuing constitutional modernization. A comprehensive characteristic of constitutional prospects for changing the form of government in Ukraine, taking into account the experience of political reform in 2004 and 2014, as well as the current state of development of the system of state power of Ukraine.
Keywords: конституційний процес; глава держави; президент; конституційне право; форма правління; повноваження глави держави; constitutional process; head of state; president; constitutional law; form of government; powers of the head of state